Metabolic Syndrome (MetS) and Nonalcoholic Steatohepatitis (NASH): Study of biochemical markers Free Fatty Acid (FFA), Total Antioxidant Status (TAOS), Adiponectin, Transforming Growth Factor (TGF-beta1), in occurence of NASH - Agus Sulaeman; A Rifai Amiruddin; Gatot Susilo Lawrence (The Prodia Education and Research Institute (PERI), 2009)
BACKGROUND: The prevalence of metabolic syndrome (MetS) in USA and Makassar are 22% and 23.7%. The prevalence of Non Alcoholic Steatosis Hepatosis (NASH) in MetS has not been reported. Study in Non-alcoholic Fatty Liver Disease (NAFLD) is 25–90 % in obesity patients. In NASH, there is accumulation of lipid in hepatocyte (raised free fatty acid level), raised stress oxidative (decreased total antioxidant status), raised of inflammation process (decreased adiponectin) and hepatic fibrotic process (raised TGF β1). The aim of this study is to investigate the correlation of free fatty acid, total antioxidant status, adiponectin and TGF-β1 with the occurrence of NASH.METHODS: This was a case control study in man aged ≥30 years old. Metabolic syndrome (MetS) was defined by IDF categories. NASH was defined as fatty liver plus raised type IV collagen level ≥140 ng/ml and Alanine Transferase (ALT) level 1.5x upper normal limit.RESULT: The samples consisted of 8 MetS subjects, 11 MetS subjects with fatty liver and 2 MetS subjects with suspect NASH. Low level of adiponectin and high level free fatty acid led to progression from Fatty Liver (FL) to NASH. Level of total antioxidant and Level of TGF-β1 were relatively steady in NASH.CONCLUSION: The level of Free Fatty acid in subjects with MetS-FL was higher than in subjects with MetS, but was lower than in subjects with MetS-NASH. No difference in total antioxidants status level was observed among all groups. Level of adiponectin decreased in subjects with MetS-FL and MetS-NASH compared with subjects with MetS only. The level of TGF-β1 increased in subjects with MetS-FL more than in subjects with MetS only, and was steady low in subjects with MetS-NASH.KEYWORDS: metabolic syndrome, NASH, free fatty acid, total antioxidant status, adiponectin, transforming growth factor β1